Commercialization and Pasisir Culture - Djoko Suryo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1996)
Commercialization process and the establishment of coastal culture in Javawas one united history process where one cannot be separated from the other. The commercialization process and the establishment of the coastal culture cannot be separated from the commercialization process and the establishment of Malay World in South East Asia. In other words, we can say that basically, commercialization process and the establishment of the coastal culture had been part of commercialization process and the establishment of the Malay World. Commercialization process and the establishment of Malay World and coastal culture was a manifestation of the united Mainstreams of commercialization and Islamization processes being occured in South East Asia of Malay World.